Egg Consumption and Stroke Risk: A Systematic Review and Dose-Response Meta-Analysis of Prospective Studies - Tang, Hui; Cao, Yi; Yang, Xiang; Zhang, Yuekang (Frontiers in Nutrition, 2020)
Background: The present study was performed to systematically quantify the association between egg consumption and stroke risk as inconsistent results have been produced. Methods: Three electronic databases (PubMed, Embase, and Cochrane Library), previous reviews, meta-analyses, and bibliographies of relevant articles were retrieved from prospective cohort studies published before July 1, 2020. The random-effects model was employed to estimate summary relative risks (RRs) and 95% confidence intervals (CIs). A dose-response analysis was also performed when data were available. Results: Sixteen publications involving 24 prospective cohort studies were included in our final meta-analysis. No significant association between egg consumption and stroke risk was identified (RR = 0.92, 95% CI: 0.84–1.01) for the highest vs. the lowest quintiles of egg intake. Subgroup analysis indicated that geographic location significantly modified the effect of egg consumption on stroke risk. Higher egg consumption was attributed to a reduced probability of stroke in Asia (RR = 0.83, 95% CI: 0.73–0.94), but not in North America (RR = 0.95, 95% CI: 0.77–1.16) or Europe (RR = 1.02, 95% CI: 0.91–1.16). Dose-response analysis demonstrated a nearly J-shaped curve between egg consumption and risk of stroke. A decreased risk was observed for the intake of one to four eggs weekly and an increased risk for the intake of more than six eggs weekly. The results were significant at an intake of 10 eggs weekly. Conclusions: The evidence from this meta-analysis showed that a J-shaped association exists between egg consumption and stroke risk.